Disraeli's Disciple : The Scandalous Life of George Smythe - Millar, Mary S., 1939- (Book collections on Project MUSE., 2006)
She also documents Smythe's numerous and often disreputable love affairs with remarkable partners: the French countess thirty years his senior, the Anglican priest who wrote him passionate poetry, the circus equestrienne he groomed for marriage to an Earl, and the Scottish heiress he married as he lay dying of tuberculosis." "In addition to the portrait it paints of a fascinating man whose public life was as earnest and idealistic as his private life was shocking and titillating, Disraeli's Disciple also provides new insights into the politics of this formative stage in British history."--Jacket.